INCREASING CHILDREN’S ENGLISH ABILITY THROUGH READING WORD MEDIA ANDROID-BASED IN OASIS KIDS NATIONAL PLUS SCHOOL GROUP B ACADEMIC YEAR 2018/2019 - Anjar Fitrianingtyas; Jumiatmoko Jumiatmoko; Nurul Shofiatin Zuhro (Early Childhood Education and Development Journal, 2019)
This research is a Class Action Research which aims to improve English ability of group B consist of 7 children. This research was conducted in two cycles and each cycle consist of five stages that are planning, implementing actions, observing and reflecting. Data collection method used observation, interview and documentation. Data analysis technique used qualitative descriptive technique. The results showed the achievement of indicators and an increase in English ability. It can be seen from the pre-cycle English ability in the good category of 14.28%, then in the first cycle increased to 21.43% and in the second cycle the English ability of children increased by 75%. The conclusion of this research is that through the reading word media android-based can improve English ability of children in Oasis Kids National Plus School in Group B academic year 2018/2019. There is a suggestion for educators to try improving children’s English ability by using a variety of learning media, one of which is to use reading word media android-based. In addition, a suggestion for schools is to be a place for early childhood education to be able to provide learning activities in accordance with the characteristics of children’s learning abilities.